On the occurrence of Didymosperma nanum H. Wendl. & Drude (Arecaceae) in Bangladesh - Uddin, Mohammad Zashim; Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2006)
Not available. Key words: Arecaceae, Didymosperma nanum, Bangladesh DOI: 10.3329/bjpt.v13i2.587 Bangladesh J. Plant Taxon. 13(2): 171-172, 2006 (December)